The practice of strengthening the base of a slab foundation of a multi-story building with soil-cement elements - Krysan, Vladimir; Krysan, Vitali; Hasenko, Anton (Academic journal Industrial Machine Building Civil Engineering, 2022)
The characteristic geotechnical conditions of modern high-rise construction are considered. The engineering and geological conditions of the site were analyzed. In particular, it was noted that loose soils lie up to a depth of 2.2 m, and below 13.0…13.5 – eolian-deluvial deposits (sandy and silty loams with a deformation modulus of 5…7 MPa). The territory is flooded. An effec-tive constructive-technological solution was tested using the drilling-mixing method of placing soil-cement elements to strength-en the base made of highly compressible clay soils under the slab foundation of a multi-story residential building with a parking lot under the conditions of the existing building. The results of tests of soil cement samples, which were selected during the execution of works, for uniaxial compression are presented.
Keywords: engineering and geological element; eolian-deluvial deposits; ground base; vertical soil-cement element; slab foundation; testing of cement soil for uniaxial compression; soil deformation modulus; settlement